Comparison of biological properties of [177Lu]Lu‐ProBOMB1 and [177Lu]Lu‐NeoBOMB1 for GRPR targeting. (11th January 2020) - Rousseau, Etienne; Lau, Joseph; Zhang, Zhengxing; Zhang, Chengcheng; Kwon, Daniel; Uribe, Carlos F.; Kuo, Hsiou‐Ting; Zeisler, Jutta; Bratanovic, Ivica; Lin, Kuo‐Shyan; Bénard, François
Abstract: The gastrin‐releasing peptide receptor (GRPR) is overexpressed in prostate cancer and other solid malignancies. Following up on our work on [ 68 Ga]Ga‐ProBOMB1 that had better imaging characteristics than [ 68 Ga]Ga‐NeoBOMB1, we investigated the effects of substituting 68 Ga for 177 Lu to determine if the resulting radiopharmaceuticals could be used with a therapeutic aim. We radiolabeled the bombesin antagonist ProBOMB1 (DOTA‐pABzA‐DIG‐D‐Phe‐Gln‐Trp‐Ala‐Val‐Gly‐His‐Leu‐ψ‐Pro‐NH2 ) with lutetium‐177 and compared it with [ 177 Lu]Lu‐NeoBOMB1 (obtained in 54.2 ± 16.5% isolated radiochemical yield with >96% radiochemical purity and 440.8 ± 165.1 GBq/μmol molar activity) for GRPR targeting. Lu‐NeoBOMB1 had better binding affinity for GRPR than Lu‐ProBOMB1 ( K i values: 2.26 ± 0.24 and 30.2 ± 3.23nM). [ 177 Lu]Lu‐ProBOMB1 was obtained in 53.7 ± 5.4% decay‐corrected radiochemical yield with 444.2 ± 193.2 GBq/μmol molar activity and >95% radiochemical purity. In PC‐3 prostate cancer xenograft mice, tumor uptake of [ 177 Lu]Lu‐ProBOMB1 was 3.38 ± 1.00, 1.32 ± 0.24, and 0.31 ± 0.04%ID/g at 1, 4, and 24 hours pi. However, the uptake in tumor was lower than [ 177 Lu]Lu‐NeoBOMB1 at all time points. [ 177 Lu]Lu‐ProBOMB1 was inferior to [ 177 Lu]Lu‐NeoBOMB1, which had better therapeutic index for the organs receiving the highest doses. Abstract : A lutetium bombesin derivative targeting the gastrin‐releasing peptide receptor was evaluated in a model of prostate cancer. Our data suggests that the selection of radiometal can adversely affect tumor uptake and pharmacokinetics of ProBOMB1.